2011
DOI: 10.1002/etc.643
|View full text |Cite
|
Sign up to set email alerts
|

Development of biotic ligand models for chronic manganese toxicity to fish, invertebrates, and algae

Abstract: Ecotoxicity tests were performed with fish, invertebrates, and algae to investigate the effect of water quality parameters on Mn toxicity. Models were developed to describe the effects of Mn as a function of water quality. Calcium (Ca) has a protective effect on Mn toxicity for both fish and invertebrates, and magnesium (Mg) also provides a protective effect for invertebrates. Protons have a protective effect on Mn toxicity to algae. The models derived are consistent with models of the toxicity of other metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…These toxicity tests were conducted at 25 °C in a natural soft water (hardness = 12 mg L –1 CaCO 3 , Ca = 4 mg L –1 ) with a pH of 6.7 and 12 mg L –1 DOC. Although the DOC was 4 times higher than that in Magela Creek water (typically <3 mg L –1 ; Supplemental Data, Table S1), DOC has been reported to have less influence on Mn toxicity compared with other physicochemical parameters .…”
Section: Methodsmentioning
confidence: 97%
“…These toxicity tests were conducted at 25 °C in a natural soft water (hardness = 12 mg L –1 CaCO 3 , Ca = 4 mg L –1 ) with a pH of 6.7 and 12 mg L –1 DOC. Although the DOC was 4 times higher than that in Magela Creek water (typically <3 mg L –1 ; Supplemental Data, Table S1), DOC has been reported to have less influence on Mn toxicity compared with other physicochemical parameters .…”
Section: Methodsmentioning
confidence: 97%
“…Although the impact of hardness on metal speciation and bioavailability is well known (Lebrun et al, 2011;Peters et al, 2011;Heijerick et al, 2003;Wright and Frain, 1981), its influence on the physiology of organisms, in particular on the density of sites of action of metal transporters, and subsequently on the accumulation of metals in organisms, has been poorly studied to date. Ma et al (1999) showed that Cu uptake in Ceriodaphnia dubia did not change when organisms were grown in water with high or low Ca 2þ concentration levels.…”
Section: 2mentioning
confidence: 98%
“…Because the aim of most WQBs is to protect organisms from long‐term exposures that can occur throughout their life cycle, predictions of chronic toxicity, rather than acute toxicity, are considered most relevant for generic WQB adjustment (Niyogi and Wood ). The need for BLMs that predict the toxicity of chronic metal exposures has long been recognized, and chronic BLMs have been developed for Cu, Pb, Mn, Ni, and Zn (Heijerick et al ; De Schamphelaere and Janssen ; Peters, Lofts et al ; Peters, Merrington et al ; Nys et al ). Although the focus has been primarily on freshwater ecosystems, BLMs have also been developed for the marine environment (e.g., USEPA ).…”
Section: Strengths Limitations and Potential Applications Of Water mentioning
confidence: 99%